Edelweiss: A Story - Auerbach, Berthold, 1812-1882; Frothingham, Ellen, 1835-1902 (Salt Lake City, UT : Project Gutenberg, 2010)
"Edelweiss: A Story" by Berthold Auerbach is a fictional narrative likely written in the late 19th century. The book explores themes of family, loss, and personal growth, centered around young Lenz, who grapples with the recent death of his mother. As the characters navigate their grief and the relationships within their village, the story delves into the enduring impact of love and memory. The opening of the narrative introduces a series of poignant moments following the funeral of Lenz's mother, who is deeply revered by the community. The young protagonist is depicted preparing for the upcoming changes, receiving counsel from various characters who share their thoughts about his mother and the life ahead. As Lenz interacts with family members and friends, including a long-time companion who has painted his mother$1 (Bs portrait, it becomes evident that the emotional landscape of the story not only highlights Lenz's sorrow but also hints at potential avenues for healing and resilience. The rich details of the setting and conversations serve to create a vivid backdrop against which the themes of grief and community play out, setting the stage for Lenz$1 (Bs journey of self-discovery and the revisiting of cherished memories. (This is an automatically generated summary.)s
Release date is 2010-06-28
Produced by Charles Bowen, from books scans provided by Google Books
Keywords: German fiction -- Translations into English